Qualitative assessment of public facilities: the "public bus". Issue 2 (14th March 2016) - Das, Shreya; Pandit, Debapratim
Abstract : Purpose: – The purpose of this paper is to develop a method to benchmark the service quality of any public facility based on users' perception, by taking the case of "bus design". While some researchers have defined level of service (LOS) for highways, transit system and pedestrian facility to measure their service quality, limited attempt has been made to measure users' perception of service quality for other public facilities which cannot be described by quantitative service levels. Design/methodology/approach: – In this research, an average weighted scoring technique has been integrated with the method of successive interval scaling to develop a five graded LOS scale that benchmarks users' perception of service quality for "bus design". The method has been exemplified by taking five types of buses currently operating in Kolkata that represent five types of "bus design". This method can be applied for other public facilities. Findings: – By applying the method an LOS scale from LOS A to LOS E was developed for "bus design" in Kolkata that represent users' perception from "very good" to "very poor". "Bus design" has been described by a list of attributes identified in this research. "Degree of criticality" of different design attributes based on users' requirements was used to identify the key attributes for improvement which was also found to vary for different bus user groups in Kolkata. Originality/value: – This research is the first ever attempt to benchmark service quality of a qualitative facility like "bus design" based on users' perception instead of expert opinion as used by previous researchers.